Increasing Local Original Income: Implementation of Tourism Sector Development Policy in Indonesia - Wahid, Nur; Rusliadi, Rusliadi; Bahri, Andi Iqra Syamsul (Universitas Padjadjaran, 2025)
If the tourism sector is not well managed, uncontrolled growth and excessive waste can damage the environment and reduce its economic potential. The impact will make it difficult for someone to create jobs. This research aims to analyse the implementation of a tourism development policy in increasing local revenue in Bulukumba Regency. Researchers used qualitative methods, research data obtained from observation, interviews, documentation, and media review. In the data analysis process, researchers used Nvivo 12 plus software. This research indicates that tourism development efforts in Bulukumba have produced positive results. The Tourism Office as the main implementer and the community as a supporter. Government and community involvement in the policy implementation process and establishing strategic programmes. This is evidenced by the communication during the implementation of tourism policies that runs by transmitting information to all stakeholders. The implementation of disposition has shown positive results in terms of optimising human resources. However, the persistence of the problem of overlapping responsibilities in the bureaucratic structure hinders the achievement of optimal performance. This research can contribute to the government to further strengthen cooperation in policy implementation and management of the tourism sector in various regions to improve people's welfare.